Development and evaluation of radio frequency management approaches for stratospheric communication systems - Abdykadyrov, Askar; Abdullayev, Mukhit; Kuttybayeva, Ainur; Tazhen, Kalmukhamed; Kystaubayev, Nurlan; Ermekbayev, Muratbek; Meshcheryakova, Tatyana; Turebekova, Altynkul; Sarsenbayev, Nurlan (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is the methods of radio frequency resource management in stratospheric communication systems based on high altitude platform stations (HAPS). The problem addressed is the limited radio frequency spectrum, frequency overlap with fifth- and sixth-generation (5G/6G) networks, and the high probability of interference, which complicate efficient spectrum utilization and coordination. The obtained results indicate that within the frequency bands recommended by the International Telecommunication Union (ITU) — 21.4–22.0 GHz, 24.25–27.5 GHz, 47.2–47.5 GHz, and 47.9–48.2 GHz — the probability of interference reaches up to 70% in the 27.5–28.35 GHz band. By applying cognitive radio (CR) technology, interference levels decreased by 60%, and spectrum utilization efficiency increased by 35%. Dynamic spectrum access (DSA) improved spectrum efficiency by 30–45%, while spectrum sharing methods enhanced it by 40–60%. A brief explanation of the results shows that the proposed management approaches significantly increase the efficiency of radio frequency resource use and substantially reduce interference. For example, at a bandwidth of 100 MHz and a signal-to-noise ratio (SNR) of 10, the channel capacity reached approximately 332 Mbps. The distinctive features of the results lie in the comprehensive use of modern technologies that effectively address spectrum scarcity and interference issues, ensuring compatibility of HAPS with existing terrestrial and satellite communication systems. The proposed approaches are suitable for implementation in international and national spectrum coordination and licensing frameworks aimed at expanding broadband connectivity in underserved regions